2019
DOI: 10.1002/jbio.201900202
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of moisture influenced cadaveric tympanic membrane using phase shift‐resolved optical Doppler vibrography

Abstract: An elevated relative moisture in the external ear canal and middle ear cavity may predispose to chronic otorrhea and related infections along with abnormal tympanic membrane (TM) vibration patterns. Therefore, phase shift-resolved optical Doppler vibrography (ODV) was used for vibration assessments of moisture influenced cadaveric TM. ODV was applied to generate time resolved cross-sectional and volumetric vibrographs of a cadaveric TM, driven acoustically at several frequencies. In order to analyze the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…However, these methods have a major disadvantage, i.e., insufficient resolution and necessity of ultrasonic transmission media. Optical coherence tomography (OCT) has the capabilities of noncontact, noninvasive, nonionizing, and highresolution scanning with various biomedical applications [25][26][27][28]. OCT has been well-utilized for various studies in dentistry such as for the detection of dental caries and gingival sulcus and the evaluation of dental abfraction and attrition [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods have a major disadvantage, i.e., insufficient resolution and necessity of ultrasonic transmission media. Optical coherence tomography (OCT) has the capabilities of noncontact, noninvasive, nonionizing, and highresolution scanning with various biomedical applications [25][26][27][28]. OCT has been well-utilized for various studies in dentistry such as for the detection of dental caries and gingival sulcus and the evaluation of dental abfraction and attrition [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Nitraatmeststoffen stimuleren de opname van positief geladen ionen als K + terwijl ammonium de opname reduceert (Zhang et al 2010;Marschner, 2011). Verder spelen chemischfysische eigenschappen, onder andere pH, in de bodem en biologische factoren zoals micro-organismen (Bhaduri et al 2014;Fierer, 2017;Jeon, 2019) een belangrijke rol. Bemesting heeft bijvoorbeeld ook effect op de microbiële activiteit in de bodem/het substraat en kan daarmee indirect een secundaire cascade van effecten op plantafweer en tolerantie induceren mede doordat bodem gebonden pathogenen in staat zijn nutriënten te immobiliseren.…”
Section: Effect Op Ziekteontwikkelingunclassified
“…Moreover, in terms of detecting the effusions in the tympanic cavity, which is required to choose the appropriate therapeutic strategies, Kirsten et al [70] demonstrated the possibility of Doppler OCT as a tool to indirectly measure the scattering and transparent fluids. Since non-invasive detection of the fluid in the tympanic cavity is difficult when using otoscopy and tympanometry, the selection of proper therapeutic strategy depends on the expertise of the physician.…”
Section: Human Cadaveric Experimentsmentioning
confidence: 99%